FOLKLORE-MIRROR OF OUR VALUES (Multidisciplinary Journal of Science and Technology, 2024)
this article reflects on the folklore art of the Uzbek people, folklore-ethnographic communities and the history of their development.Our national value and the history of musical folklore and the process of education and upbringing in musical folklore. Samples from folk song performance are widely covered.